Analisis Motivasi Belajar Siswa Kelas X.3 dengan Menggunakan Model Pembelajaran Tutorial pada Mata Pelajaran Informatika di UPT SMA Negeri 3 Maros - Nafisah Nafisah; Fathihatus Sholihah; M. Risal; Muhajir Muhajir; Nasir Nasir (Pusat Riset dan Inovasi Nasional, 2024)
The use of the tutorial learning model in Informatics subjects is the focus of attention in efforts to create a learning environment that motivates and encourages active student involvement. This research aims to provide a holistic understanding of the effectiveness of using the tutorial learning model in class X.3 at UPT SMA Negeri 3 Maros. This research uses quantitative descriptive research methods. The results of this research show that students' learning motivation in using the tutorial learning model is in the high category with an average percentage of 79.1%, so it can be concluded that the tutorial learning model is quite effective for use in informatics learning.